Reflective Practices of Papuan EFL Teachers in the EFL Classroom - Rahmawansyah Sahib; Tegar Aulia (English Department - University of Sultan Ageng Tirtayasa, 2025)
Enhancing teachers’ professionalism and competence has long been a fundamental priority in education. For EFL (English as a Foreign Language) teachers in Papua, reflective practice is essential for addressing classroom challenges and improving teaching quality. This study examines the models of reflective practice adopted by Papuan EFL teachers across different school levels. Using a qualitative descriptive approach, data were gathered from five EFL teachers at elementary, junior high, and senior high schools through classroom observations, interviews, and document analysis, and then analyzed thematically. The findings identify three primary models of reflective practice. First, reflective teaching activities, such as asking thought-provoking questions at the beginning, during, and at the end of lessons, which stimulate student engagement and teachers’ self-assessment. Second, reflective writing, including teaching journals, diaries, and notes documenting students’ feedback and teachers’ impressions, fostering continuous professional growth and awareness. Third, dialogical reflection, involving debates, informal discussions, and sharing experiences with fellow teachers, which encourages collaborative learning and peer support. These findings underscore the importance of developing a formal, long-term policy framework to institutionalize reflective practice among EFL teachers in Papua. Such a framework would help ensure that reflective activities are systematic, result-oriented, and significantly contribute to improving teaching effectiveness and student learning outcomes.